PREDICTIVE MODELING OF Mimosa tenuiflora (WILLD) POIRET: HOW CAN CLIMATE CHANGE AFFECT ITS POTENTIAL DISTRIBUTION RANGE? - Chagas, Kyvia Pontes Teixeira das; Lucas, Fernanda Moura Fonseca; Vieira, Fábio de Almeida (Floresta, 2020)
Studies that characterize the effects of climatic factors on the geographic distribution of arboreal individuals are of fundamental importance, especially for widely exploited species of wood potential, such as Mimosa tenuiflora (Willd) Poiret (jurema-preta). In this sense, the objective of this work was to predict the climatically adequate areas for the occurrence of Mimosa tenuiflora, present (1960-1990) and future (2070). We used the Maxent algorithm to relate the occurrence records of the species to the climatic variables. For the year 2070, we test two scenarios and three general atmospheric circulation models, HadGEM2-ES, GISS-E2-R and MIROC-ESM. Modeling for the present presented an AUC index (area under the curve) of 0.94 (± 0.02), indicating a good fit of the model used. For the future scenario, the AUC value ranged from 0.88 to 0.89 and 0.87 to 0.88 for the optimistic and pessimistic scenarios, respectively. The highest percentage of contribution was to the annual precipitation variable. The areas of adequacy occupied the states of Ceará and Rio Grande do Norte in higher intensity and almost all of them. When compared to the present, the geographic territory with high suitability for the future presented a reduction from 28.7% to 53.7% in the optimistic scenario and 30.9% to 59.4% in the pessimistic scenario. The information obtained can be used as a subsidy for the establishment of commercial plantations, the definition of management and conservation strategies, and the creation of an in situ conservation bank for Mimosa tenuiflora species.